(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2023)
Acetamide is heavily used as a plasticizer and stabilizer and in the methylamine manufacturing process. There has been a modest but steady rise in worldwide interest in microbe-mediated acetamide decomposition or degradation as a bioremediation method. A previously isolated molybdenum-reducing bacterium with amide-degrading capability is characterized for its growth on acetamide in this study. The bacterium growth optimally in between 500 and 1000 mg/L of acetamide, an optimal pH of between 6.5 and 8.0, and optimal temperatures supporting growth of between 30 and 35 °C. Toxic heavy metals, such as mercury, silver and copper slowed down the growth of this bacterium on acetamide. Growth of acetamide exhibits potent inhibition on growth as evidenced from the considerable lag phase that increases as the concentrations of acetamide was increased. As the tolerance level to acetamide for this bacterium is relatively higher than other acetamide-degrading bacteria in the literature, this bacterium can potentially be an excellent acetamide bioremediation agent.